Using the indigenous technology of organic crop farming to mediate learning in Grade 12 Agricultural Science classes - Sheehama, Lydia Ndapandula (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The Namibian Curriculum for Basic Education states clearly that Indigenous Knowledge (IK) should be integrated into science teaching. However, the irony is that it does not give clear pedagogical guidelines on how it should be integrated. The implication is that the curriculum assumes that all teachers are aware of how to integrate IK into their teaching. This assumption has therefore led to little or no integration of IK in many classrooms in Namibia, something which could be in part a contributing factor to poor learners' academic performance in science subjects and Agricultural Science in particular. This tension in the curriculum plus the apparent gap in the literature regarding the integration of IK has triggered my interest to conduct this interventionist qualitative case study. Essentially, this study aimed to explore affordances and/or hindrances when using the indigenous technology of organic crop farming to mediate learning in Grade 12 Agricultural Science classes in peri-urban schools in the Oshana region in Namibia. The study was underpinned by the interpretivist and Ubuntu paradigms. Vygotsky's (1978) socio-cultural theory and Shulman's (1986) pedagogical content knowledge (PCK) framework were used as lenses to analyse my data. Within PCK, I also used Mavhunga and Rollnick's (2013) Topic-Specific PCK as an analytical framework. The findings of the study revealed that the integration of Indigenous knowledge in Agricultural Science education has great potential in improving both the teaching and learnng of science. It also revealed that the Agricultural Science teachers were positive towards the integration of IK in their lessons. However, they conceded that they lacked pedagogical insights on how to integrate IK as they were never trained on how to integrate it. As a result, they found the presentations by the Indigenous Knowledge Custodians (IKCs) informative and shed light on how they could integrate IK during teaching and learning. That is, they became cultural knowledge brokers making science relevant and accessible to their learners. The study thus recommends that teacher training institutions should modify the curriculum to include a pedagogy course module on IK to equip students with the essential PCK on IK integration in science teaching.
Keywords: Agricultural science; Ethnoscience; Traditional knowledge; Organic farming; Pedagogical content knowledge